History of Educational Institutions Named After Borys Grinchenko as a Form of Representation of Pedagogical Biography - Matviichuk, Oksana; Petroshchuk, Natalia (Educological discourse, 2024)
The article highlights and summarizes the history of the creation and activity of educational institutions named after Borys Grinchenko in the cities of Kyiv, Bila Tserkva, Lviv, Kharkiv, Uman, and Poltava Oblast. Examples of successful graduates of these institutions are given, and the names of teachers who worked in them are partially established. It is argued that Borys Grinchenko is a Ukrainian pedagogue, writer, ethnographer, and political figure, whose name is inscribed in the annals of national revival. Materials were found about individuals who participated in perpetuating the memory of Borys Grinchenko. It is noted that the gratitude of descendants for a person who made a noticeable mark in life as an individual or society in general can be manifested in different ways. Most often, honoring the memory of a person and his contribution to the development of science, education, culture, politics and other spheres of public life is manifested in the naming of a specific person to a street, alley, educational institution, which is issued by an order, and public discussion takes place. The research uses the methods of pedagogical biography, which in a structural dimension covers the life path and creative achievements of pedagogical personalities. It is noted that the actualization of research is strengthened in the conditions of today, when the past is understood, evaluated, compared with the present through the biographies of famous or less famous figures who, thanks to their life and creative successes, have become symbols of certain historical periods. The study of the history of educational institutions named after Borys Grinchenko as a form of representation of pedagogical biography made it possible to outline the main approaches to honoring the memory of Borys Grinchenko. It was concluded that separate comprehensive studies of the history of educational institutions named after Borys Grinchenko as a form of representation of pedagogical biography are not enough, which indicates the relevance and novelty of the materials of this article.